Design and baseline characteristics of participants in the TRial of Economic Incentives to Promote Physical Activity (TRIPPA): A randomized controlled trial of a six month pedometer program with financial incentives - Finkelstein, Eric Andrew (Elsevier, 2016)
Contemporary Clinical Trials